Development of Coffea canephora Pierre ex A. Froehner transplants cultivated in different substrates and containers - Silva, Janaína Iara; Vieira, Henrique Duarte; Viana, Alexandre Pio; Barroso, Deborah Guerra (Coffee Science - ISSN 1984-3909, 2010)
In coffee transplant production, substrate is one of the factors limiting growth. The ideal substrate should meet the oxygen, water and nutrient requirements for normal plant growth. The objective of this work was to verify the effect of different substrates and containers on the growth of coffee transplants in the nursery, and also to develop a new methodology for producing Coffea canephora Pierre ex A. Froehner transplants using agroindustrial residues. The following containers were used: polyethylene bags, conical tubettes with 80 cc and 120 cc capacity and pressed blocks (mixture of organic material). Each treatment corresponded to one type of substrate and one type of container. The results showed that organic material may be a potential substrate for C. canephora transplant production. The transplants produced in the organic material, organic material + controlled nutrients, soil + cow manure + controlled nutrients substrates presented the best results for all the traits compared, in relation to the other substrates, indicating that they are the best option for producing coffee transplants. The pressed block, polyetilene bags and big size tubettes may be appropriate containers for C. canephora transplant production. The commercial substrate was inadequate for coffee transplant production, regardless of the container.